IMPLEMENTASI PENDIDIKAN ANTI KORUPSI BERBASIS MODEL PROBLEM BASED LEARNING MELALUI FILM ‘SEBELUM PAGI TERULANG KEMBALI - Tri Adi Setiawan; Muhamad Iqbal (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
This research departs from the phenomenon that is motivated by moral degradation in Indonesia, one of which is corrupt behavior in social and state life. Even education, which should be a place to instill virtue values, can become a means of corruption. This worrying condition due to the problem of corruption can hinder the achievement of public welfare, this problem can be overcome, one of which is by taking preventive measures such as providing anti-corruption education in formal schools. This anti-corruption education can be integrated through the Problem Based Learning with film media. The approach used in this research is a case study approach, which is intended to understand the object being studied specifically as a case. Data was collected through observation, interviews and documentation studies. The purpose of this research is to find out; First the planning process of Problem Based learning through film media in fostering the character of honesty in students. Second the process of implementing Problem Based learning through film media in fostering the character of honesty in students. Finally obstacle factors and solutions to Problem Based learning through film media in fostering the character of honesty in students. The results of this study indicate that by applying the Problem Based Learning learning model with film media, it is found that around 88% of students during learning have shown attitudes and behaviors that reflect anti-corruption behavior in the school environment as well as in learning. From the description above, the researcher concludes that the application of the problem-based learning model through film media can increase the attitude of 'honest' anti-corruption behavior in students.